Pityriasis rubra pilaris following administration of SARS‐CoV‐2 vaccine - Shumpei Kondo; Yasuaki Ogura; Masaki Ohtsuka; Yoshiki Tokura (Journal of Cutaneous Immunology and Allergy, 2023)
Pityriasis rubra pilaris (PRP) is a rare, chronic, inflammatory dermatosis characterized by follicular, hyperkeratotic papules and palmoplantar keratoderma at any age. The exact etiology of the disease remains unknown, but it can be triggered by multiple factors and genetic backgrounds. Here, we describe a case of PRP occurring after SARS‐CoV‐2 vaccination. While the vaccination is generally safe, it should be kept in mind that PRP may be evoked by SARS‐CoV‐2 vaccination for early recognition of the cause and prognosis of the patients.